The role of long distance contribution to the B → K⁎ℓ+ℓ− in the Standard Model - Massimo Ladisa; Pietro Santorelli (Physics Letters B, 2023)
We investigate rare semileptonic B→K⁎ℓ+ℓ− by looking at a specific long distance contribution. Our analysis is limited to the very small values of physical accessible range of invariant mass of the leptonic couple q2. We show that the light quarks loop has to be accounted for, along with the charming penguin contribution, in order to accurately compute the q2-spectrum in the Standard Model. Such a long distance contribution may also play a role in the analysis of the lepton flavor universality violation in this process.